CDKN2A Polymorphism in Melanoma Patients in Colombian Population: A Case-Control Study. (12th October 2020) - Tovar-Parra, Jose D.; Gutiérrez-Castañeda, Luz D.; Gil-Quiñones, Sebastián R.; Nova, Jhon A.; Pulido, Leonardo
Abstract : Introduction . Melanoma is the most aggressive type of skin cancer, with poor prognosis in advanced stages. The incidence and mortality rates have increased in recent years. Single nucleotide polymorphisms p.R24P, p.M53I, p.G101W, p.V126D, and p.A148T in the CDKN2A (HGNC ID: 1787) gene have been associated with the development of melanoma in different populations; however, this association has not been studied in Colombia. Methods . Cutaneous melanoma patients and healthy controls (85 cases and 166 controls) were included in this study. These subjects were screened through HRM-qPCR assay and detected variants in exon 1 and 2 of CDKN2A gene and confirmed with Sanger sequencing. Chi-square test was used to compare allele and genotype distributions between cases and controls. Odds ratio (OR) with 95% confidence interval (CI) was calculated to determine the association between polymorphisms and haplotypes with melanoma susceptibility. Statistical and haplotype analyses were performed using Stata® and R-Studio®. Results . Fifty-four percent of women were identified both in cases and controls. The frequencies of melanoma subtypes were 36, 47% lentigo maligna, 24, 71% acral lentiginous, 23, 53% superficial extension, and 15, 29% nodular. Variants in the CDKN2A gene were 11.76% in cases and 8.43% in controls. The most frequent was p.A148T in 5.88% of cases and in 4.82% of controls. GGTTG haplotype showed statistically significant differences between cases and controls (p value = 0.04). Conclusion . CDKN2A polymorphisms p.G101W, p.R24P, p.M53I, and A148T are not associated with melanoma susceptibility in the Colombian population; further studies regarding genetic interaction and additive effects between more variants are required.